The Functional Illiteracy and Accounting: An Exploratory Study with Undergraduate Students of Institutions of Higher Education of the State of Espírito Santo - João Carlos Hipólito Bernardes do Nascimento; Valcemiro Nossa; Moisés Balassiano (Revista Sociedade, Contabilidade e Gestão, 2013)
Functional illiteracy comprises citizens with limited ability to read, write and perform basic calculations inherent to social and professional life, despite having access to the formal education system. Considering the present scenario of judgment about the essence of form arising from the convergence to International Financial Reporting Standards (IFRS), the present study aimed to investigate whether functional illiteracy is a relevant phenomenon using a sample of students from an undergraduate course in Accounting. Using a questionnaire with items from the 1993 National Assessment of Adult Literacy – NAAL, a model was derived using the True Score from Item Response Theory as the dependent variable, and applying Cluster Analysis and Logistic Regression techniques. As a result, it was noted that functional illiteracy is relevant to senior’s undergraduate Accounting students, given that 40% showed evidence of the phenomenon. The seniors presented a percentage of overall accuracy of approximately 45% in document skills, quantitative skills and verbal skills. This deficit evaluated the ability to apply new information to make inferences, the ability of decision-making and, ultimately, quantitative and computational capacity. Given these results, we can conclude that the minimizing functional illiteracy negatively impacts, minimizing the learning and, in second time when students are in the labor market, deteriorating the quality of the information generated.